Enhancement of methane production in mesophilic anaerobic digestion of secondary sewage sludge by advanced thermal hydrolysis pretreatment. (15th March 2015) - Abelleira-Pereira, Jose M.; Pérez-Elvira, Sara I.; Sánchez-Oneto, Jezabel; de la Cruz, Roberto; Portela, Juan R.; Nebot, Enrique
Abstract: Studies on the development and evolution of anaerobic digestion (AD) pretreatments are nowadays becoming widespread, due to the outstanding benefits that these processes could entail in the management of sewage sludge. Production of sewage sludge in wastewater treatment plants (WWTPs) is becoming an extremely important environmental issue. The work presented in this paper is a continuation of our previous studies with the aim of understanding and developing the advanced thermal hydrolysis (ATH) process. ATH is a novel AD pretreatment based on a thermal hydrolysis (TH) process plus hydrogen peroxide (H2 O2 ) addition that takes advantage of a peroxidation/direct steam injection synergistic effect. The main goal of the present research was to compare the performance of TH and ATH, conducted at a wide range of operating conditions, as pretreatments of mesophilic AD with an emphasis on methane production enhancement as a key parameter and its connection with the sludge solubilization. Results showed that both TH and ATH patently improved methane production in subsequent mesophilic BMP (biochemical methane potential) tests in comparison with BMP control tests (raw secondary sewage sludge). Besides other interesting results and discussions, a promising result was obtained since ATH, operated at temperature (115 °C), pretreatment time (5 min) and pressure (1 bar) considerably below those typically used in TH (170 °C, 30 min, 8 bar), managed to enhance the methane production in subsequent mesophilic BMP tests [biodegradability factor ( f B ) =  cumulative CH 4 production / cumulative CH 4 production (Control)  = 1.51 ± 0.01] to quite similar levels than conventional TH pretreatment [ f B  = 1.52 ± 0.03]. Graphical abstract: Highlights: Thermal hydrolysis (TH) and advanced thermal hydrolysis (ATH) anaerobic digestion pretreatments are studied. Both TH and ATH patently improved total methane production in mesophilic BMP tests. Higher solubilization of secondary sewage sludge not always entails an improvement on BMP. ATH at 115 °C, 5 min, 1 bar shows quite similar performance than TH at 170 °C, 35 min, 8 bar. Pretreatments at 115 °C did not increase the H2 S content in the biogas from BMP tests.